2009
DOI: 10.1073/pnas.0813037106
|View full text |Cite
|
Sign up to set email alerts
|

Prevention of autoimmune disease by induction of tolerance to Toll-like receptor 7

Abstract: Activation of Toll-like receptors (TLR) contributes to the initiation and maintenance of chronic inflammation in autoimmune diseases, yet repeated exposure to a TLR agonist can induce hyporesponsiveness to subsequent TLR stimulation. Here, we used a synthetic TLR7 agonist, 9-benzyl-8-hydroxy-2-(2-methoxyethoxy) adenine (SM360320, 1V136) to study TLR7 induced attenuation of inflammatory responses and its application to autoimmune diseases. Repeated low dose administration of this TLR7 agonist induced hyporespon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
101
0
3

Year Published

2010
2010
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(110 citation statements)
references
References 39 publications
6
101
0
3
Order By: Relevance
“…In the only study examining this concept in EAE, tolerance induction using TLR7 ligands was shown to attenuate active immunization (i.e., not adoptive transfer) EAE models (23). However, in that study, it was also demonstrated that the TLR7 ligands cross-tolerized to TLR2.…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…In the only study examining this concept in EAE, tolerance induction using TLR7 ligands was shown to attenuate active immunization (i.e., not adoptive transfer) EAE models (23). However, in that study, it was also demonstrated that the TLR7 ligands cross-tolerized to TLR2.…”
Section: Discussionmentioning
confidence: 86%
“…TLR tolerance in autoimmunity, although investigated in a murine model of type 1 diabetes (28), has rarely been studied in the context of either TLR2 or EAE (23,28). In the only study examining this concept in EAE, tolerance induction using TLR7 ligands was shown to attenuate active immunization (i.e., not adoptive transfer) EAE models (23).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Significantly, FcgRIIB-deficient mice develop lupus-like symptoms, indicating the importance of these inhibitory mechanisms in maintaining self-tolerance (36). The role of SHIP-1 in TLR7-dependent tolerance induction and development of autoimmunity has been demonstrated in a murine model of autoimmune encephalitis (42). Critically, both IL-1R-associated kinase IRAK-M and SHIP-1 are upregulated in response to prestimulation of cells with TLR7 agonists and subsequently negatively regulate cytokine production following subsequent treatment of cells with TLR2, TLR7, and TLR9 ligands (42).…”
Section: Discussionmentioning
confidence: 99%
“…The role of SHIP-1 in TLR7-dependent tolerance induction and development of autoimmunity has been demonstrated in a murine model of autoimmune encephalitis (42). Critically, both IL-1R-associated kinase IRAK-M and SHIP-1 are upregulated in response to prestimulation of cells with TLR7 agonists and subsequently negatively regulate cytokine production following subsequent treatment of cells with TLR2, TLR7, and TLR9 ligands (42). These recent studies highlight the importance of SHIP-1 as a negative regulator of TLR signaling and its potential importance in autoimmunity.…”
Section: Discussionmentioning
confidence: 99%